Can avoidance of complications lead to biased healthcare decisions? - Jennifer Amsterlaw; Brian J. Zikmund-Fisher; Angela Fagerlin; Peter A. Ubel (Judgment and Decision Making, 2006)
Imagine that you have just received a colon cancer diagnosis and need to choose between two different surgical treatments. One surgery, the "complicated surgery," has a lower mortality rate (16% vs. 20%) but compared to the other surgery, the "uncomplicated surgery," also carries an additional 1% risk of each of four serious complications: colostomy, chronic diarrhea, wound infection, or an intermittent bowel obstruction. The complicated surgery dominates the uncomplicated surgery as long as life with complications is preferred over death.